Biodegradable and absorbable hemostatic composition and application thereof

By optimizing the composition of water-soluble polysaccharides and sodium carboxymethyl starch, hemostatic granules were prepared, which solved the problems of limited biocompatibility and hemostatic effect of existing hemostatic materials, and achieved faster hemostasis and healing effects.

CN120983690AActive Publication Date: 2025-11-21CHONGQING DATSING MEDICAL DEVICE CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511501057.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2025-11-21
Estimated Expiration
2045-10-21

AI Technical Summary

Technical Problem

Existing hemostatic materials suffer from poor biocompatibility, are prone to causing allergic reactions, have poor degradation and absorption properties, and have limited hemostatic effects.

Method used

A biodegradable hemostatic composition comprising water-soluble polysaccharides and sodium carboxymethyl starch was used to prepare hemostatic granules via wet granulation technology. The component ratio and particle size were optimized to improve water absorption and adhesion.

Benefits of technology

It significantly improves water absorption, adhesion, and hemostasis time, shortens the complete healing time, and enhances the hemostatic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120983690A_ABST
    Figure CN120983690A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable and absorbable hemostatic composition and application thereof, and belongs to the technical field of medical materials. The technical problems that an existing hemostatic material is poor in biocompatibility, prone to causing anaphylactic reaction, poor in degradation and absorption performance, limited in hemostatic effect and the like are solved. According to the technical scheme, the hemostatic composition is characterized by being prepared from the following components in parts by weight: 0.03 to 10 parts of water-soluble polysaccharide and 90 to 99.97 parts of sodium carboxymethyl starch, the water-soluble polysaccharide is prepared from sodium hyaluronate, sodium alginate, carboxymethyl chitosan and carboxymethyl cellulose according to the mass ratio of (8 to 10): (0 to 2): (0 to 2): (0 to 2); the molecular weight of the sodium carboxymethyl starch is 105-106, and the substitution degree of the sodium carboxymethyl starch is 0.2-0.6%; the particle size of the hemostatic composition is 100-500 [mu] m, and the bulk density of the hemostatic composition is 0.2-0.3 g / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of medical materials technology and provides a biodegradable and absorbable hemostatic composition and its application. Background Technology

[0002] For understanding the technical content of this invention: Following bleeding from external injuries or surgery, failure to stop the bleeding promptly can lead to infection and further trauma. In such cases, hemostatic materials play a crucial role. Besides excellent hemostatic properties, hemostatic materials should also possess good biocompatibility and biodegradability. Currently, commonly used medical hemostatic materials include polysaccharide hemostatic materials such as cellulose and starch, collagen hemostatic materials such as gelatin, biological hemostatic materials such as thrombin, and synthetic hemostatic materials such as polyethylene glycol and cyanoacrylate. Different hemostatic materials have different hemostatic mechanisms; therefore, how to combine them to achieve the best hemostatic effect is a key research focus in this field.

[0003] Relevant non-patent literature retrieved: The journal or book title is *Journal of Regional Anatomy and Surgery*, and the article title is "Study on the Use of Decellularized Porcine Small Intestinal Submucosal Powder for Hemostasis in Partial Splenectomy Wounds in Rats," Volume 30, Publication Date: December 2021. This article discloses that after degreasing and decellularization, SIS powder has no residual cells, and under a microscope, the SIS powder appears as a single-layer, long, thin sheet. The water absorption rate of the SIS powder reaches saturation at 120 seconds, which is 1.87 times that of instant hemostatic powder. Furthermore, the SIS powder is biodegradable in vivo and has broad application prospects.

[0004] Relevant patent documents retrieved: This document, published in China (CN117679552A) on December 9, 2023, discloses a hemostatic sponge, its preparation method, and its application. The raw materials for preparing the hemostatic sponge include a water-soluble polysaccharide solution and decellularized small intestinal submucosal particles; the mass ratio of the decellularized small intestinal submucosal particles to the water-soluble polysaccharide solution is (0.1-0.9):1. During use, the porous structure of the hemostatic sponge rapidly absorbs water from blood and tissue fluid, causing the polysaccharide components to dissolve into a viscous solution that adheres to the wound surface for hemostasis. The growth factors in the decellularized small intestinal submucosal particles promote wound healing, and the particles maintain a triple helix structure, thereby causing platelet aggregation, activation, and release of granular components, accelerating the release of coagulation factors and further promoting wound healing.

[0005] The prior art represented by the aforementioned documents has at least the following unresolved technical problems or defects: (1) SIS powder has limited effect when used alone. The relevant evidence is that SIS is mostly used as a scaffold material to load other hemostatic materials. Its hemostatic effect and mechanism still need further research.

[0006] (2) When SIS particles and water-soluble polysaccharide solution are combined, their hemostatic effect is limited. The relevant evidence is that although they have good adhesion (viscosity modulus of more than 40 GPa), their water absorption rate is insufficient (only about 30%), which limits the hemostatic effect and the wound healing effect. At the same time, they are spongy, which is inconvenient to use on uneven and irregular wound surfaces. Summary of the Invention

[0007] The purpose of this invention is to provide: A biodegradable and absorbable hemostatic composition and its application, and related technologies, to solve the technical problems of existing hemostatic materials, such as poor biocompatibility, easy to cause allergic reactions, poor degradation and absorption performance, and limited hemostatic effect, or a combination thereof.

[0008] Terminology Explanation: Unless otherwise defined, all technical terms used herein have the same meanings as commonly understood by one of ordinary skill in the art. Unless otherwise stated, all patents, patent inventions, and publications cited in this document are incorporated herein by reference in their entirety. If multiple definitions exist for terms, the definition provided in this chapter shall prevail.

[0009] It should be understood that the above brief description and the following detailed description are exemplary and for illustrative purposes only, and do not limit the subject matter of the invention in any way. In this invention, the singular is used in conjunction with the plural unless otherwise specifically stated. It should also be noted that, unless otherwise stated, the use of “or” or “or” means “and / or”. Furthermore, the use of the term “comprising” and other forms such as “including,” “containing,” and “contains” are not limiting.

[0010] The definition of the standard chemical term can be found in the reference "Modern Drugs and Clinical Diagnosis and Treatment, edited by Guo Fang et al., Changchun: Jilin Science and Technology Press, 2021.07."

[0011] Unless otherwise stated, conventional methods within the scope of the art, such as wet granulation, shall be used.

[0012] Unless specifically defined herein, the use of all commercially available products herein employs standard techniques. For example, it may be carried out using the manufacturer's instructions for use with the kit, or in accordance with methods known in the art or the description of this invention. The techniques and methods described herein can generally be implemented according to conventional methods well known in the art, based on the descriptions in the various summary and more specific documents cited and discussed in this specification.

[0013] The terms “optional / arbitrary” or “optionally / arbitrarily” mean that the event or situation described below may or may not occur, including both the occurrence and non-occurrence of the event or situation.

[0014] The term "water-soluble polysaccharide" as used in this article refers to a class of heteropolysaccharides, also known as glycosaminoglycans or acidic polysaccharides. They are composed of two or more different monosaccharide molecules, typically containing uronic acid and aminohexose or their derivatives.

[0015] The term "sodium carboxymethyl starch" used in this article, also known as carboxymethyl starch, is an anionic starch ether, a type of modified starch, belonging to the ether starch family, and is a water-soluble anionic polymer compound. It has strong water absorption and swelling properties, and can swell quickly in cold water.

[0016] The term "small intestinal submucosa" used in this article refers to the submucosa obtained from the small intestine of pigs, cattle, sheep, dogs, etc., especially pigs. A suitable length of intestinal segment is taken, mechanically wiped to obtain the submucosa, and then decellularized. It is mainly composed of type I and type III collagen (>90%), and also contains trace amounts of other extracellular matrix components such as fibronectin, hyaluronic acid, and cytokines (including FGF-2 and TGF-β). It possesses good mechanical properties, tissue compatibility, and low immunogenicity, making it a commonly used natural scaffold material in tissue engineering research.

[0017] The term "molecular weight" as used herein refers to relative molecular mass, and unless otherwise specified in this invention, it refers to weight-average molecular weight.

[0018] The term “degree of substitution” as used in this article refers to the degree to which the hydroxyl group on each D-glucopyranose unit of a starch molecule is replaced by a carboxymethyl group, that is, the average number of −CH2COONa-CH2COONa functional groups on each D-glucopyranose unit.

[0019] The term "%" used in this article refers to mass (weight) percentage.

[0020] In a first aspect, the present invention provides: a biodegradable and absorbable hemostatic composition, wherein the hemostatic composition comprises, by weight, 0.03-10 parts of water-soluble polysaccharide and 90-99.7 parts of sodium carboxymethyl starch; wherein the water-soluble polysaccharide is composed of sodium hyaluronate, sodium alginate, carboxymethyl chitosan and carboxymethyl cellulose in a mass ratio of 8-10:0-2:0-2:0-2; The sodium carboxymethyl starch has a molecular weight of 10. 5 -10 6 The degree of substitution is 0.2-0.6%; The hemostatic composition has a particle size of 100-500 μm and a bulk density of 0.2-0.3 g / cm³. 3 .

[0021] The technical features include: the composition of the biodegradable and absorbable hemostatic composition, the composition of the water-soluble polysaccharide, the molecular weight and degree of substitution of sodium carboxymethyl starch, and the particle size and bulk density of the hemostatic composition.

[0022] The hemostatic composition with the technical feature of being biodegradable and absorbable is selected from the following components by weight: 0.03-10 parts of water-soluble polysaccharide and 90-99.97 parts of sodium carboxymethyl starch.

[0023] The preferred composition of the biodegradable and absorbable hemostatic composition is as follows: the hemostatic composition comprises, by weight, 0.03-5 parts of water-soluble polysaccharide and 95-99.97 parts of sodium carboxymethyl starch.

[0024] The composition of the biodegradable and absorbable hemostatic composition is further preferably as follows: the hemostatic composition comprises, by weight, 1 part of water-soluble polysaccharide and 99 parts of sodium carboxymethyl starch.

[0025] The water-soluble polysaccharide composition of the technical feature is selected from sodium hyaluronate, sodium alginate, carboxymethyl chitosan and carboxymethyl cellulose in a mass ratio of 8-10:0-2:0-2:0-2.

[0026] The preferred composition of the water-soluble polysaccharide is: sodium hyaluronate, sodium hyaluronate and sodium alginate in a mass ratio of 8-10:0.1-2. Specifically, the mass ratio of sodium hyaluronate to sodium alginate includes, but is not limited to, 10:0.1, 9:0.1, 8:0.1, 10:0.5, 9:0.5, 8:0.5, 10:1, 9:1, 8:1, 5:1, 4.5:1, and 4:1; or sodium hyaluronate and carboxymethyl chitosan in a mass ratio of 8-10:0.1-2. Specifically, the mass ratio of sodium hyaluronate to carboxymethyl chitosan includes, but is not limited to, 10:0.1, 9:0.1, 8:0.1, 10:0.5, 9:0.5, 8:0.5, and 10:1. 9:1, 8:1, 5:1, 4.5:1, and 4:1; or sodium hyaluronate and carboxymethyl cellulose in a mass ratio of 8-10:0.1-2, specifically, the mass ratio of sodium hyaluronate and carboxymethyl cellulose includes, but is not limited to: 10:0.1, 9:0.1, 8:0.1, 10:0.5, 9:0.5, 8:0.5, 10:1, 9:1, 8:1, 5:1, 4.5:1, and 4:1; or sodium hyaluronate, sodium alginate, and carboxymethyl chitosan in a mass ratio of 8-10:0.1-2:0.1-2, specifically, the mass ratio of sodium hyaluronate, sodium alginate, and carboxymethyl chitosan includes, but is not limited to: 10:2:2, 10:1:2, 10:0.1:2, and 10:2. :1, 10:2:0.1, 10:1:1, 10:1:0.1, 10:0.1:1:, 10:0.1:0.1, 9:2:2, 9:1:2, 9:0.1:2, 9:2:1, 9:2:0.1, 9:1:1, 9:1:0.1, 9:0.1:1:, 9:0.1:0.1, 8:2:2, 8:1:2, 8:0.1:2, 8:2:1, 8:2:0.1, 8:1:1, 8:1:0.1, 8:0.1:1 and 8:0.1:0.1; or sodium hyaluronate, sodium alginate and carboxymethyl cellulose in a mass ratio of 8-10:0.1-2:0.1-2, specifically, sodium hyaluronate, sodium alginate and carboxymethyl cellulose The mass ratios of vitamins include, but are not limited to: 10:2:2, 10:1:2, 10:0.1:2, 10:2:1, 10:2:0.1, 10:1:1, 10:1:0.1, 10:0.1:1:, 10:0.1:0.1, 9:2:2, 9:1:2, 9:0.1:2, 9:2:1, 9:2:0.1, 9:1:1, 9:1:0.1, 9:0.1:1:, 9:0.1:0.1, 8:2:2, 8:1:2, 8:0.1:2, 8:2:1, 8:2:0.1, 8:1:1, 8:1:0.1, 8:0.1:1, and 8:0.1:0.1; or mass ratios of 8-10:0.1-2:0.The composition is 1-2 parts sodium hyaluronate, carboxymethyl chitosan, and carboxymethyl cellulose. Specifically, the mass ratio of sodium hyaluronate, carboxymethyl chitosan, and carboxymethyl cellulose includes, but is not limited to: 10:2:2, 10:1:2, 10:0.1:2, 10:2:1, 10:2:0.1, 10:1:1, 10:1:0.1, 10:0.1:1:, 10:0.1:0.1, 9:2:2, 9:1:2, 9:0.1:2, 9:2:1, 9:2:0.1, 9:1:1, 9:1:0.1, 9:0.1:1:, 9:0.1:0.1, 8 Sodium hyaluronate, sodium alginate, carboxymethyl chitosan, and carboxymethyl cellulose in a mass ratio of 8-10:0.1-2:0.1-2:0.1-2, or 8:2:0.1:2, 8:1:1, 8:1:0.1, 8:0.1:1, and 8:0.1:0.1; or sodium hyaluronate, sodium alginate, carboxymethyl chitosan, and carboxymethyl cellulose in a mass ratio of 8-10:0.1-2:0.1-2:0.1-2. Specifically, the mass ratio of sodium hyaluronate, sodium alginate, carboxymethyl chitosan, and carboxymethyl cellulose includes, but is not limited to: 10:2:2:2, 10:1:2:2, 10:2:1:2, 10:2:2:1, 10:1:1:2, 1 0:1:2:1, 10:1:2:2, 10:1:1:1, 10:0.1:1:1, 10:1:0.1:1, 10:1:1:0.1, 10:0.1:0.1:1, 10:0.1:1:0.1, 10:1:0.1:0.1, 10:0.1:0.1:0.1, 9:2:2:2, 9:1:2:2, 9:2:1:2, 9:2:2:1, 9:1:1:2, 9:1:2:1, 9:1:2:2, 9:1:1:1, 9:0.1:1:1, 9:1:0.1:1, 9:1 The following are some common abbreviations in Chinese characters: :1:0.1, 9:0.1:0.1:1, 9:0.1:1:0.1, 9:1:0.1:0.1, 9:0.1:0.1:0.1, 8:2:2:2, 8:1:2:2, 8:2:1:2, 8:2:2:1, 8:1:1:2, 8:1:2:1, 8:1:2:2, 8:1:1:1, 8:0.1:1:1, 8:1:0.1:1, 8:1:1:0.1, 8:0.1:0.1:1:0.1, 8:1:0.1:0.1, and 8:0.1:0.1:0.1.

[0027] The water-soluble polysaccharide composition is further preferably: sodium hyaluronate; or sodium hyaluronate, sodium alginate, and carboxymethyl chitosan in a mass ratio of 8-10:1-2:1-2. Specifically, the mass ratio of sodium hyaluronate, sodium alginate, and carboxymethyl chitosan includes, but is not limited to: 10:2:2, 10:1:2, 10:2:1, 10:1:1, 10:1:0.1, 9:2:2, 9:1:2, 9:2:1, 9:1:1, 8:2:2, 8 Sodium hyaluronate, carboxymethyl chitosan, and carboxymethyl cellulose in a mass ratio of 1:2, 8:2:1, and 8:1:1; or sodium hyaluronate, carboxymethyl chitosan, and carboxymethyl cellulose in a mass ratio of 8-10:1-2:1-2. Specifically, the mass ratio of sodium hyaluronate, carboxymethyl chitosan, and carboxymethyl cellulose includes, but is not limited to: 10:2:2, 10:1:2, 10:2:1, 10:1:1, 9:2:2, 9:1:2, 9:2:1, 9:1:1, 8:2:2, 8:1:2, 8:2:1, and 8:1:1.

[0028] The water-soluble polysaccharide composition of the technical feature is further preferably: sodium hyaluronate; or sodium hyaluronate, sodium alginate and carboxymethyl chitosan in a mass ratio of 8:1:1; or sodium hyaluronate, carboxymethyl chitosan and carboxymethyl cellulose in a mass ratio of 8:1:1.

[0029] The technical feature of decellularized small intestinal submucosal particles is selected from any one of the following: decellularized porcine small intestinal submucosal particles, decellularized bovine small intestinal submucosal particles, decellularized sheep small intestinal submucosal particles, and decellularized dog small intestinal submucosal particles.

[0030] The preferred technical feature of the decellularized small intestinal submucosal particles is any one of the following: decellularized porcine small intestinal submucosal particles, decellularized bovine small intestinal submucosal particles, decellularized sheep small intestinal submucosal particles, and decellularized dog small intestinal submucosal particles with a particle size of 30-50μm (including but not limited to 30μm, 35μm, 40μm, 45μm, and 50μm).

[0031] The decellularized submucosal particles of the small intestine are further preferably decellularized porcine submucosal particles with a particle size of 30-40μm (including but not limited to 30μm, 35μm, and 40μm).

[0032] The preferred technical feature is that the decellularized submucosal particles of the small intestine are decellularized porcine submucosal particles with a particle size of 35 μm.

[0033] Among them, the technical feature of sodium carboxymethyl starch is selected from: a molecular weight of 10 5 -10 6 Sodium carboxymethyl starch with a degree of substitution of 0.2-0.6%.

[0034] The preferred technical feature of sodium carboxymethyl starch is: a molecular weight of 1×10⁻⁶. 5 -5×10 5 Sodium carboxymethyl starch with a degree of substitution of 0.2-0.5%.

[0035] The preferred technical feature of sodium carboxymethyl starch is: a molecular weight of 5 × 10⁻⁶. 5 Sodium carboxymethyl starch with a degree of substitution of 0.2-0.3%.

[0036] The preferred technical feature of sodium carboxymethyl starch is: a molecular weight of 5 × 10⁻⁶. 5 Sodium carboxymethyl starch with a degree of substitution of 0.2%.

[0037] Based on further solutions to the technical problems of the present invention, or simultaneous solutions to multiple technical problems, the preferred solution in the technical solution provided in the first aspect of the present invention includes: The first preferred embodiment is: the water-soluble polysaccharide is sodium hyaluronate, sodium hyaluronate in a mass ratio of 8-10:1-2:1-2, carboxymethyl chitosan, and sodium alginate, or sodium hyaluronate, carboxymethyl chitosan, and carboxymethyl cellulose in a mass ratio of 8-10:1-2:1-2. This technical solution, having already solved the technical problems of "increasing water absorption rate to over 18%, increasing viscous modulus to over 40 Pa, while achieving hemostasis time within 42 seconds and complete healing time within 14 days," further solves the technical problems of "increasing water absorption rate to over 79%, increasing viscous modulus to over 42 Pa, while achieving hemostasis time within 16 seconds and complete healing time within 9 days."

[0038] The second preferred embodiment: the molecular weight of the sodium carboxymethyl starch is 1×10⁻⁶. 5 -5×10 5 The degree of substitution is 0.2-0.5%. This technical solution, having already addressed the technical issues of "increasing water absorption rate to over 18%, increasing viscous modulus to over 40 Pa, while maintaining hemostasis time within 42 seconds and complete healing time within 14 days," further addresses the technical issues of "increasing water absorption rate to over 80%, increasing viscous modulus to over 42 Pa, while maintaining hemostasis time within 15 seconds and complete healing time within 8.5 days."

[0039] The third preferred embodiment: the hemostatic composition has a particle size of 100-250 μm and a bulk density of 0.3 g / cm³. 3This technical solution, having already solved the technical problems of "increasing water absorption rate to over 18%, increasing viscous modulus to over 40 Pa, while keeping hemostasis time within 42 seconds and complete healing time within 14 days," further solves the technical problems of "increasing water absorption rate to over 80%, increasing viscous modulus to over 46 Pa, while keeping hemostasis time within 16 seconds and complete healing time within 8.5 days."

[0040] The fourth preferred embodiment: the hemostatic composition further includes decellularized small intestinal submucosal particles; by weight, the hemostatic composition includes: 0.03-10 parts of water-soluble polysaccharide, 90-99.97 parts of sodium carboxymethyl starch, and 1-10 parts of decellularized small intestinal submucosal particles. This technical solution, having already solved the technical problems of "increasing water absorption rate to over 18%, increasing viscous modulus to over 40 Pa, while maintaining hemostasis time within 42 seconds and complete healing time within 14 days," further solves the technical problems of "increasing water absorption rate to over 80%, increasing viscous modulus to over 46 Pa, while maintaining hemostasis time within 16 seconds and complete healing time within 8.5 days."

[0041] Fifth preferred embodiment: The biodegradable and absorbable hemostatic composition is prepared by the following method: (1) Dissolve each component of the water-soluble polysaccharide in water to form a water-soluble polysaccharide solution; (2) The decellularized submucosal granules of small intestine and sodium carboxymethyl starch were thoroughly mixed to obtain a mixture, which was then sprayed into a water-soluble polysaccharide solution for wet granulation to obtain wet granules; (3) The wet granules are granulated, dried and sterilized to obtain the final product.

[0042] The technical features include: water-soluble polysaccharide solution and wet granulation.

[0043] The concentration of the water-soluble polysaccharide solution is selected from 0.5-3 wt%.

[0044] The preferred concentration of the water-soluble polysaccharide solution is 0.5-2 wt%.

[0045] The concentration of the water-soluble polysaccharide solution is further preferably 0.5-1 wt%.

[0046] The concentration of the water-soluble polysaccharide solution is further preferably 1 wt%.

[0047] The technical features of the wet granulation process are selected from the following conditions: the temperature of the mixture is 30-35℃; the speed of the peristaltic pump is 5-10 r / min.

[0048] The preferred technical features of the wet granulation process are: the temperature of the mixture is 32-35℃; and the peristaltic pump speed is 5-8 r / min.

[0049] Among them, the technical features of the wet granulation process are further optimized as follows: the temperature of the mixture is 32℃; the speed of the peristaltic pump is 5r / min.

[0050] Among them, the technical feature of wet granulation process conditions is selected from: spray gun pressure of 0.2-0.3MPa.

[0051] Among them, the preferred wet granulation process conditions are: spray gun pressure of 0.2 MPa.

[0052] Secondly, the present invention provides the application of the above-mentioned biodegradable and absorbable hemostatic composition in the preparation of medical hemostatic products.

[0053] The beneficial effects of this invention are as follows: Compared with existing technologies, the present invention has better technical effects in terms of water absorption rate, adhesion, hemostasis time, and complete healing time.

[0054] According to experimental tests, the present invention increases the water absorption rate from less than 18% in the prior art to more than 79%.

[0055] According to experimental tests, the present invention increases the adhesion modulus from 40 Pa in the prior art to over 42 Pa.

[0056] According to experimental tests, the present invention reduces the hemostasis time from more than 30 seconds in the prior art to less than 16 seconds.

[0057] According to experimental tests, the present invention reduces the complete healing time from more than 10 days in the prior art to less than 8.5 days. Attached Figure Description

[0058] Figure 1 A photograph showing the appearance of the hemostatic granules prepared in Example 1 of this invention; Figure 2 This is a SEM image of the hemostatic granules prepared in Example 1 of the present invention. Detailed Implementation

[0059] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0060] The present invention will be further described below by way of specific embodiments. Unless otherwise specified, all instruments, devices, equipment, reagents, products, etc., used in the embodiments of the present invention are obtained through conventional commercial means.

[0061] The raw materials used in the embodiments of this invention are sourced from the following sources: Sodium hyaluronate was purchased from Bloomage Biotechnology Co., Ltd. Carboxymethyl chitosan was purchased from Chongqing Daqing Haide Technology Co., Ltd. Sodium alginate was purchased from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd. Carboxymethyl cellulose was purchased from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd. Sodium carboxymethyl starch was purchased from Anhui Shanhe Pharmaceutical Excipients Co., Ltd.

[0062] Preparation of decellularized porcine small intestinal submucosal layer (SIS) particles: Following the method described in the literature "Experimental study on the effect of decellularization treatment on residual cells and growth factor content in the small intestinal submucosal layer" (Chen Wei, Li Cihui, Wu Shu, Xie Huiqi, Luo Jingcong (2010) Chinese Journal of Reparative and Reconstructive Surgery v.24(01):94-99), commercially available fresh porcine jejunum within 4 hours was cleaned, disinfected, and then mechanically peeled, defatted, decellularized, degreased, and freeze-dried. The SIS particles were then ground into microparticles with a particle size of 30-50 μm using a grinder at -80℃.

[0063] Example 1 A biodegradable and absorbable hemostatic composition is prepared as follows: (1) Dissolve 3.0g of mixed water-soluble polysaccharide in 300ml of purified water and stir evenly to make it completely dissolved to obtain a water-soluble polysaccharide solution with a concentration of 1wt%; wherein, the mixed water-soluble polysaccharide is sodium hyaluronate, carboxymethyl chitosan and sodium alginate in a mass ratio of 8:1:1.

[0064] (2) Mix 27g of SIS particles (particle size 50μm) and sodium carboxymethyl starch (molecular weight 5×10⁻⁶). 5 270g of a mixture (with a substitution degree of 0.2%) was added to a fluidized bed granulator at a mass ratio of 1:10. The fan frequency was set to 25Hz, the total air pressure to 0.44MPa, the airtight pressure to 0.14MPa, and the spray gun pressure to 0.2MPa. After heating for 20 minutes, the material temperature reached approximately 32℃. Then, liquid feeding (spraying in a water-soluble polysaccharide solution) was initiated, with the peristaltic pump feed rate set to 5r / min. After granulation and drying, the product was sieved through 150-mesh and 60-mesh screens to obtain particles with a diameter of 100-250μm and a bulk density of 0.3g / cm³. 3 Particles; (3) The granules obtained in step (2) are filled into the pusher, then placed in an aluminum foil bag and sealed, and sterilized by irradiation to obtain hemostatic granules 1.

[0065] Example 2: Regarding the composition of polysaccharides Based on Example 1, the composition of the polysaccharide was examined. Its dosage was the same as that of hemostatic granules 1, with the only difference being the composition and mass ratio, as shown in Table 1.

[0066] Table 1 Polysaccharide composition of hemostatic granules

[0067] The preparation method of the hemostatic granules is the same as in Example 1.

[0068] Detection Example 1 The basic properties of hemostatic granules 1-7 were tested, and the test indicators and specific methods are as follows: (1) Water absorption rate: Wet the filter paper in the Bush funnel (40 mm in diameter) with distilled water. After the funnel stops dripping, time for 10 minutes. Place the wet filter paper in a glass dish and weigh the filter paper as m1. Accurately weigh approximately 0.2 g (accurate to 0.001 g) of the sample and record it as m. Sprinkle the sample evenly on the filter paper in the Bush funnel. Pour in 20 ml of water. After the funnel stops dripping, time for 10 minutes. Place the wet filter paper and wet sample in a glass dish and measure the mass of the filter paper and wet sample as m2. Calculate the water absorption rate using the following formula: Water absorption rate = (m2-m1) / m.

[0069] (2) Adhesion: After the hemostatic granules have completely absorbed water, the viscosity modulus G'' of the hemostatic granules after water absorption is tested using a TA rheometer. The equipment parameters are: temperature 37℃, deformation 1%, and frequency 0.9Hz.

[0070] The results of water absorption and adhesion of hemostatic granules 1-7 are shown in Table 2.

[0071] Table 2 Results of water absorption and adhesion of each hemostatic granule

[0072] Test Example 2: Animal Hemostasis and Healing Test The above-mentioned hemostatic granules were used to repair wounds in rabbits (2.5kg). The specific process was as follows: After disinfecting a 5×5cm area on the back of the rabbit with the fur removed, a 1×1cm incision was made on the back with a scalpel. 1g of each of the above-mentioned hemostatic granules was applied to the surface of the wound, and the hemostasis of the wound was observed and the hemostasis time was recorded. At the same time, the wound healing was observed every 12 hours until the rabbit's wound was completely healed. The infection and healing time of the rabbit's wound were recorded. The results are shown in Table 3.

[0073] Table 3 Hemostatic effects of various hemostatic granules

[0074] As shown in Tables 2 and 3, compared to hemostatic granules 8 without added polysaccharides, the addition of viscous polysaccharides allows SIS granules and sodium carboxymethyl starch to physically and effectively combine, forming porous and uniformly mixed microparticles. This increases the water absorption rate and the product's adhesiveness, enabling it to effectively adhere to the wound surface and improve hemostasis efficiency. However, different polysaccharide compositions result in varying degrees of differences in the water absorption performance or viscosity modulus of the hemostatic granules. Among them, hemostatic granules 1-3, containing sodium hyaluronate polysaccharide, exhibit higher water absorption rates and viscosity moduli, shorter hemostasis and complete healing times, and the best hemostatic effect.

[0075] Example 3: Regarding the molecular weight and degree of substitution of sodium carboxymethyl starch Based on Example 1, the molecular weight and degree of substitution of sodium carboxymethyl starch were investigated. The specific molecular weight and degree of substitution of sodium carboxymethyl starch are shown in Table 4.

[0076] Table 4. Molecular weight and degree of substitution of sodium carboxymethyl starch

[0077] The preparation method of the hemostatic granules is the same as in Example 1.

[0078] Detection Example 3 The water absorption rate, adhesion, and hemostatic effect of the above-mentioned hemostatic granules were evaluated according to the methods of test examples 1 and 2. The results are shown in Table 5.

[0079] Table 5. Water absorption rate, adhesion, and hemostatic effect of each hemostatic granule

[0080] As can be seen from Table 5, excessively high molecular weight and insufficient substitution, or excessively low molecular weight and excessive substitution, will lead to varying degrees of reduction in water absorption rate and viscous modulus, which in turn will prolong hemostasis time and healing time, and worsen the hemostasis and healing promotion effect.

[0081] Detection Example 4 Take 1g each of hemostatic granules 1, 9, 10, 11 and 12, connect them to the endoscope tube through the pusher device, and spray them onto a petri dish containing 15ml of distilled water using simulated abdominal pressure. Record the spraying status and the time it takes for each hemostatic granule to completely absorb the water. The results are shown in Table 6.

[0082] Table 6. Water absorption of hemostatic granules

[0083] Compared with hemostatic granules 1, 10, and 11, hemostatic granule 9 has a large molecular weight, low degree of substitution, poor hydrophilicity, and slow water absorption rate. After complete water absorption, it may over-swell, increase in volume, cause compression, increase viscosity, and delay the aggregation of coagulation factors. Hemostatic granule 12 has a small molecular weight, high degree of substitution, and strong hydrophilicity. It is easy to form a water film on the surface, which affects the water absorption rate.

[0084] Example 4: Regarding the ratio of sodium carboxymethyl starch, water-soluble polysaccharide, and SIS particles. Based on Example 1, the dosage of water-soluble polysaccharide, SIS particles and sodium carboxymethyl starch was investigated. The specific raw material composition is shown in Table 7.

[0085] Table 7 Dosage of water-soluble polysaccharides, SIS granules, and sodium carboxymethyl starch

[0086] Among them, the water-soluble polysaccharide of hemostatic granules 13 is sodium hyaluronate; the water-soluble polysaccharides of hemostatic granules 14 and 15 are the same as those of hemostatic granules 1.

[0087] The preparation method of the hemostatic granules is the same as in Example 1.

[0088] Case 5 The water absorption rate, adhesion, and hemostatic effect of the above-mentioned hemostatic granules were evaluated according to the methods of test examples 1 and 2. The results are shown in Table 8.

[0089] Table 8. Water absorption rate, adhesion, and hemostatic effect of each hemostatic granule

[0090] As can be seen from Table 8, water-soluble polysaccharides, SIS particles, and sodium carboxymethyl starch, when mixed in a certain ratio, all have high water absorption and viscosity modulus, and exhibit good hemostatic and healing-promoting effects.

[0091] Example 5: Regarding the particle size range and bulk density of hemostatic granules Based on Example 1, the particle size range and bulk density of the hemostatic particles were investigated. The particle size range was obtained by sieving through sieves of different mesh sizes, and the bulk density was achieved by controlling the spray gun pressure during the preparation process. See Table 9 for details.

[0092] Table 9. Particle size range and bulk density of hemostatic granules

[0093] The preparation method of the hemostatic granules is the same as in Example 1.

[0094] Case 6 The water absorption rate, adhesion, and hemostatic effect of the above-mentioned hemostatic granules were evaluated according to the methods of test examples 1 and 2. The results are shown in Table 10.

[0095] Table 10. Water absorption rate, adhesion, and hemostatic effect of each hemostatic granule.

[0096] As can be seen from Table 10, the particle size and bulk density of hemostatic granules have a significant impact on their water absorption and adhesion. Only within a certain range of particle size and bulk density can they have better water absorption and adhesion, thereby achieving better hemostasis and healing promotion effects.

[0097] Case 7 Hemostatic granules 1 and 16-19 were connected to the endoscope tube via a pusher device to spray onto the bleeding site, simulating abdominal pressure, and the spraying status was recorded.

[0098] The results showed that the particle size was less than 100 μm and the bulk density was less than 0.2 g / cm³. 3 During spraying, the product is easily dispersed, causing it to drift and fail to reach the entire wound surface, thus affecting the surgical field of vision. The particle size is greater than 850μm, and the bulk density is greater than 0.3g / cm³. 3 At that time, the product cannot be atomized and evenly dispersed on the wound.

[0099] Comparative Example 1 The composite microporous polysaccharide hemostatic powder was purchased from Shandong Saikesaisi Biotechnology Co., Ltd.

[0100] Comparative Example 2 A hemostatic sponge was prepared according to the components and preparation method of Example 1 in application number CN202311683472.7.

[0101] Comparative Example 3 A biodegradable and absorbable hemostatic granule, differing from Example 1 only in that it does not contain sodium carboxymethyl starch, is prepared as follows: (1) Dissolve 3.0g of mixed water-soluble polysaccharide in 300mL of purified water and stir evenly to make it completely dissolved to obtain a water-soluble polysaccharide solution with a concentration of 1wt%; wherein, the mixed water-soluble polysaccharide is sodium hyaluronate, carboxymethyl chitosan and sodium alginate in a mass ratio of 8:1:1.

[0102] (2) 27g of SIS particles (50μm in diameter) were added to a fluidized bed granulator. The fan frequency was set to 25Hz, the total air pressure to 0.44MPa, the airtight pressure to 0.14MPa, and the spray gun pressure to 0.2MPa. After heating for 20 minutes, the material temperature reached approximately 32℃. Liquid feeding (spraying in water-soluble polysaccharide solution) was then initiated. The peristaltic pump feed rate was set to 5r / min. After granulation and drying, the particles were sieved using 150-mesh and 60-mesh screens to obtain a particle size of 100-250μm and a bulk density of 0.3g / cm³. 3 Particles; (3) The granules obtained in step (2) are filled into the pusher, then placed in an aluminum foil bag and sealed, and sterilized by irradiation to obtain hemostatic granules 20.

[0103] Detection Example 8 The water absorption rate, adhesion, and hemostatic effect of the above-mentioned hemostatic granules were evaluated according to the methods of test examples 1 and 2. The results are shown in Table 11.

[0104] Table 11 Water absorption rate, adhesion, and hemostatic effect of various hemostatic materials

[0105] As can be seen from Table 11, the hemostatic granules 1 prepared by this invention have significantly better performance in all aspects than commercially available composite microporous polysaccharide hemostatic powder and the hemostatic sponge disclosed in application number CN202311683472.7. Furthermore, compared to hemostatic granules 1, hemostatic granules 20, which do not contain sodium carboxymethyl starch, show a significant decrease in water absorption rate, even though the viscosity change is not substantial, resulting in a significant extension of both hemostasis and healing time.

[0106] Case 9 During the animal hemostasis and healing experiment on the hemostatic granules 1 and hemostatic sponge, skin tissues of rabbits that had used hemostatic granules 1 and hemostatic sponge were taken at 3 days, 7 days and after complete healing, respectively. The blue reaction of starch and iodine was used to determine whether sodium carboxymethyl starch was completely degraded. At the same time, HE pathological observation was performed to determine whether SIS was completely degraded. The results are shown in Table 12.

[0107] Table 12 Degradation of raw materials for hemostatic granules 1 and hemostatic sponges

[0108] As can be seen from Table 12, sodium carboxymethyl starch remained in very small amounts after 3 days in the hemostatic granules prepared by the present invention, and was completely degraded after 7 days. The particle size of SIS decreased, and it was completely degraded during the healing process, which is closer to the wound healing period. However, in the hemostatic sponge of Comparative Example 2, a small amount of SIS particles remained after healing, and the degradation rate was slower.

[0109] Furthermore, the hemostatic granules prepared by this invention are in powder form (see the images for appearance and SEM morphology). Figure 1 and Figure 2 This powder can be more easily delivered to narrow cavities within the body via the laparoscopic extension tube for hemostasis, without the risk of disintegration during laparoscopic insertion. It can also be sprayed evenly onto uneven or irregular wound surfaces, making it superior to sponge-like powders.

[0110] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.

Claims

1. A biodegradable and absorbable hemostatic composition, characterized in that, The hemostatic composition comprises, by weight, 0.03-10 parts of water-soluble polysaccharide and 90-99.7 parts of sodium carboxymethyl starch; the water-soluble polysaccharide is composed of sodium hyaluronate, sodium alginate, carboxymethyl chitosan and carboxymethyl cellulose in a mass ratio of 8-10:0-2:0-2:0-2. The molecular weight of the sodium carboxymethyl starch is 10. 5 -10 6 The degree of substitution is 0.2-0.6%; The hemostatic composition has a particle size of 100-500 μm and a bulk density of 0.2-0.3 g / cm³. 3 .

2. The hemostatic composition according to claim 1, characterized in that, The water-soluble polysaccharide is sodium hyaluronate; or sodium hyaluronate, carboxymethyl chitosan and sodium alginate in a mass ratio of 8-10:1-2:1-2; or sodium hyaluronate, carboxymethyl chitosan and carboxymethyl cellulose in a mass ratio of 8-10:1-2:1-2.

3. The hemostatic composition according to claim 1, characterized in that, The hemostatic composition further includes: decellularized submucosal particles of small intestine; by weight, the hemostatic composition includes: 0.03-10 parts of water-soluble polysaccharide, 90-99.97 parts of sodium carboxymethyl starch and 1-10 parts of decellularized submucosal particles of small intestine.

4. The hemostatic composition according to claim 3, characterized in that, The decellularized small intestinal submucosal particles are selected from any one of the following: decellularized porcine small intestinal submucosal particles, decellularized bovine small intestinal submucosal particles, decellularized sheep small intestinal submucosal particles, and decellularized dog small intestinal submucosal particles.

5. The hemostatic composition according to claim 3, characterized in that, The particle size of the decellularized small intestinal submucosa particles is 30-50 μm.

6. The hemostatic composition according to claim 1, characterized in that, The molecular weight of the sodium carboxymethyl starch is 1×10⁻⁶. 5 -5×10 5 The degree of substitution is 0.2-0.5%.

7. The hemostatic composition according to claim 1, characterized in that, The hemostatic composition has a particle size of 100-250 μm and a bulk density of 0.3 g / cm³. 3 .

8. The use of the hemostatic composition according to any one of claims 1-7 in the preparation of medical hemostatic products.

Citation Information

Patent Citations

  • Hemostatic sponge as well as preparation method and application thereof

    CN117679552A

  • Bone wound hemostasis composition as well as preparation method and application thereof

    CN107158452A

  • Polysaccharide hemostasis composition, preparation method and application thereof

    CN109125795A

  • Medical wound tissue hemostasis and cell repair glue and adhesive tape combination and method

    CN110694101A

  • Solid dosage form of enteric solid dispersion and method for producing the same

    US20080038340A1